ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN UKM SEKTOR PERDAGANGAN DI KOTA DENPASAR - Maheswara, A.A.N Gede; Setiawina, I Nyoman Djinar; Saskara, I.A Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
This study aims: 1) To analyze whether there is significant direct effect of wages, workingn hours capital, education and the number of sales toward income of Small and Medium Enterprise (SME) in trading sector in Denpasar. 2 ) To analyze the direction of the effect of wages, woring hours, capital, education, and the number of sales toward income in the Small and Medium Enterprise (SME) of trading sector in Denpasar. 3 ) To analyze whether there is significant indirect effect of wages, working hours, capital and education to income through the number of sales in the Small and Medium Enterprise (SME) of trading sector in Denpasar.This study was conducted by the method of data collection by structured interview and obse r vation by using descriptive statistical analysis techniques and path analysis by using SPSS 16. After analyzing the result shows: 1) Wages and capital directly have possitive and significant effect toward total saves . 2) Working hours and education directly have possitive effect but have not significant effect toward total saves . 3) Wages , capital , and total saves have possitive and significant effect toward the SME income of trade sector in Denpasar city . 4) Working hours have possitive effect but have not significant toward the SME income of trade sector in Denpasar city.. 5) Education have negative effect but have not significant effect toward the SME income of trade sector in Denpasar city. 6) Wages and capital indirectly have significant effect toward the SME income of trade sector in Denpasar city though total saves . 7) Working hours and e ducation indirectly have not significant effect toward the SME income of trade sector in Denpasar city though total saves .
Keywords: Wages,Working Hours, Capital, Education, Total Sales, SM